Economic analysis of forage and livestock experiments conducted in the State of São Paulo - Miller, Stanley F.; Quinn, L. R.; Mott, G. O. (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this paper is to bring together in one place much of the pasture and livestock research experience of IRI in the State of São Paulo and to analyze it from an economic standpoint. To do so, many assumptions had to be made. Attempts were made to keep the assumptions realistic for the area in which the experiments were conducted. They undoubtedly are not, however, generally applicable to Brazil or even to many parts of the State of São Paulo. Rather, it is hoped that the procedure is sufficiently clear that decision makers may follow similar procedures, making their own assumptions, and thus answer questions covered in this report under conditions specific to their localities. From the data and assumptions made, it appears that: a) Common Pangola (Digitaria decumbens) has the highest annual rate of return of the six grasses tested. It affectively repelled the invasion of Bahia grass and maintained a relatively constant yield over time. Colonial Guinea was its nearest competitor, but it failed to maintain production over time. b) As a general statement, the use of 100 kilos of available nitrogen per hectare on Colonial Guinea grass appears to be profitable. The use of 200 kilos appears to be approximately the point where the marginal cost equals the marginal return and thus is the point of no profit. c) Both the use of stilbestrol and molasses appear to be profitable. d) Supplemental feeding ground corn meal or a low protein meal may be profitable on low quality forage if the weight advantage can be maintained during later periods. At present it is not known if it can. Additional research needs to be conducted to test this point.